The Impact of Peer-to-Peer Lending on Conventional Commercial Bank Credit in South Sumatra (2024–2025) - Elen Karlina; Rika Lidyah (Escalate : Economics and Business Journal, 2024)
This study aims to analyze the influence of Peer-to-Peer (P2P) lending on conventional commercial bank credit distribution in South Sumatra Province during the 2024–2025 period. The research problem focuses on the shift in public financing preferences from conventional banking to the rapidly growing P2P lending fintech platform. The research method used is a quantitative approach utilizing secondary data sourced from the Financial Services Authority (OJK) report. Data analysis was conducted using panel data regression with a Fixed Effect model. The dependent variable in this study is conventional commercial bank credit, while the independent variable is outstanding P2P lending, with control variables in the form of third-party funds and the number of bank offices. The results show that P2P lending has a significant effect on conventional commercial bank credit, especially in the MSME credit segment. This finding indicates a tendency for a substitution effect in certain segments, although conventional banking still dominates overall credit distribution. This study concludes that the growth of P2P lending requires conventional banks to adapt through digital innovation and collaboration to maintain the competitiveness and stability of the regional financial system.